Effects of Sports Games Combined with English Teaching on Children’s Attention and Learning Performance - Nan Jiang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The teaching principle of "music teaching" is implemented to facilitate children's learning through play and behaviour. During classroom instruction, teachers should appropriately incorporate sports competitions to foster students' interest in sports, ensure their active participation, and facilitate the development of their athletic abilities. During the primary school stage, students experience rapid development in their physical and mental attributes. The author administered oral and written English assessments to randomly selected classes from Grade 3 to Grade 6 at South Road Primary School, which is affiliated with A University. The author selected students who scored below 60 for the attention QPT test in each grade. From this group, we selected 10 students with low, average, and high attention levels. This resulted in a total of 30 students in each grade forming the control class. We compared the QPT scores between the 30 individuals in the experimental group and the 30 individuals in the control group. The experimental class and the control class exhibited a notable disparity in academic performance across grades 3 to 6. The implementation of experimental teaching resulted in significant improvements in the attention QPT scores of both the upper and lower grades in the experimental class. The study demonstrates that sustained adherence to teaching children English through sports games can effectively enhance their attention levels. Furthermore, implementing sports game teaching aligns with children's psychological characteristics and significantly enhances their performance in English learning.